Growing Person – the Anthropological Basis for the Educational Thought of John Bosco - Chrobak, Stanisław (Paedagogia Christiana, 2020)
John Bosco’s (1815-1888) anthropology, as it seems vertical, did not distract his attention from the worries of everyday life, from the world of youth and from the works he undertook for it. For the Turin educator – in his Christian understanding of human nature – human life is a vocation and mission. He emphasised that the true and lasting development of every human being has its source in his own heart, life and freedom. From the content of the works he left behind, it is obvious that he paid attention to both earthly and religious values. For Don Bosco, human being at his/her very foundations is directed towards divinity, towards heaven, towards God. This process starts from the earliest years, develops in the youthful years and is continued in later life.